2004
DOI: 10.5194/acp-4-1849-2004
|View full text |Cite
|
Sign up to set email alerts
|

Extrapolating future Arctic ozone losses

Abstract: Abstract. Future increases in the concentration of greenhouse gases and water vapour may cool the stratosphere further and increase the amount of polar stratospheric clouds (PSCs). Future Arctic PSC areas have been extrapolated from the highly significant trends 1958-2001. Using a tight correlation between PSC area and the total vortex ozone depletion and taking the decreasing amounts of ozone depleting substances into account we make empirical estimates of future ozone. The result is that Arctic ozone losses … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 38 publications
1
15
1
Order By: Relevance
“…Rex et al (2004) have shown a strong correlation between the vertically integrated ozone losses and the volume of air in which temperatures are below the NAT equilibrium point for the Arctic. Moreover, Knudsen et al (2004) found a remarkable correlation between the total ozone mass depleted in the vortex and PSC area probability in the Arctic (correlation coefficient = 0.96) which can be extended to the Antarctic. As a consequence, small changes of few degrees in the temperature might have nonnegligible impact on the computation of the depletion in the ozone column, in particular at those levels where the depletion is not complete.…”
Section: Discussionmentioning
confidence: 83%
“…Rex et al (2004) have shown a strong correlation between the vertically integrated ozone losses and the volume of air in which temperatures are below the NAT equilibrium point for the Arctic. Moreover, Knudsen et al (2004) found a remarkable correlation between the total ozone mass depleted in the vortex and PSC area probability in the Arctic (correlation coefficient = 0.96) which can be extended to the Antarctic. As a consequence, small changes of few degrees in the temperature might have nonnegligible impact on the computation of the depletion in the ozone column, in particular at those levels where the depletion is not complete.…”
Section: Discussionmentioning
confidence: 83%
“…In addition to the halogen abundance in the stratosphere, the evolution of chemical ozone depletion in the polar region depends on the temperature evolution in the polar vortex. An analysis of observations in the past has been used to estimate the increase of chemical ozone depletion with changing climate, based on the assumption that polar vortex temperatures for cold Arctic winters decrease with changing climate conditions [ Knudsen et al , 2004; Rex et al , 2006]. Here, a significant decrease of the temperatures in cold Arctic winters with changing climate conditions was not simulated, see below.…”
Section: Changes In Polar Vortex Dynamics and Chemistrymentioning
confidence: 99%
“…Further long term cooling in the Arctic winter stratosphere had resulted in a three-fold increase in PSCs, so that the stratospheric climate conditions had become significantly more favourable for ozone loss since the 1960s, an effect which considerably amplified the influence of the increasing halogen loading of the stratosphere. If these temperature trends continue into the future, Arctic ozone losses would increase until 2010-2015 and decrease only slowly afterwards (Knudsen et al, 2004). However, the cooling does not appear to be happening in all years -rather a pattern is emerging wherein the cold years get colder, but the warm years are not changing .…”
Section: Long-term Changes In the Arctic Stratospherementioning
confidence: 99%